Methodical training future teachers during training - Упатова, І. П. (Scientific notes of the pedagogical department, 2017)
The article describes various aspects of content and methodical training of future elementary school teachers during the training sessions and conditions for successful implementation; stated methodological knowledge, skills, experience activities, which are acquired by the students in the mastery of academic disciplines; analyzes the opportunities for methodological activities in the practical and independent work. The results of scientific research helped to determine the list of teaching knowledge and skills of primary school teachers.